A Study of Royal Female Power and Political Influence in Ancient Egypt: Contextualizing Queenship in the Twelfth Dynasty - Brandi D. Hill (2019)
The Twelfth Dynasty was a time for iconographic expression, new architectural designs, and titular expansion. During the dynasty, royal women began sharing iconographic attributes with ruling monarchs and for the first time the uraeus and sphinx pose became standardized for royal women. Women in the queenship position were buried similar to the pharaonic style and used cenotaph type burials. Princess Neferuptah became the first royal woman to have her name encircled within a cartouche and Sobekneferu was the first female ruler of Egypt to have full pharaonic titulary. This thesis explores the political power of Twelfth Dynasty royal women by aiming to redefine queenship to better understand the ancient Egyptian concept, analyze the iconography, as well as clarify the tenure and reign of Princess Neferuptah and Sobekneferu. The iconographic study discusses specific attributes that include the poses, the severity of their facial characteristics, surviving uraei, wig type, headgear worn, style of ears, cosmetic or natural eyes, dress, jewelry, and if represented independently or paired. Using an art historical analysis this study interprets the surviving representations of Twelfth Dynasty royal women as elevations of their royal statuses in governmental positions. It also compares their iconography to royal women of other time periods, such as the Old Kingdom through the beginning of the Eighteenth Dynasty, and with male monarchs of the Twelfth Dynasty. This project formulates ideas on the events of the late Twelfth Dynasty by describing the power exhibited by the royal women Neferuptah and Sobekneferu. It examines Neferuptah and Sobekneferu in an art historical and archaeological context by their art works, (possible) burial complexes, building projects, titled burial goods, and representations with Amenemhat III. This study includes a complete familial lineage with artifacts and the first catalogue of surviving representations of all known Twelfth Dynasty royal women.